2001
DOI: 10.1083/jcb.153.5.1049
|View full text |Cite
|
Sign up to set email alerts
|

E-Cadherin Suppresses Cellular Transformation by Inhibiting β-Catenin Signaling in an Adhesion-Independent Manner

Abstract: E-cadherin is a tumor suppressor protein with a well-established role in cell–cell adhesion. Adhesion could contribute to tumor suppression either by physically joining cells or by facilitating other juxtacrine signaling events. Alternatively, E-cadherin tumor suppressor activity could result from binding and antagonizing the nuclear signaling function of β-catenin, a known proto-oncogene. To distinguish between an adhesion- versus a β-catenin signaling–dependent mechanism, chimeric cadherin constructs were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
438
4
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 502 publications
(471 citation statements)
references
References 66 publications
22
438
4
5
Order By: Relevance
“…Recent studies have suggested that E-cadherin suppresses cell growth by inhibiting b-catenin signaling (Gottardi et al, 2001;Stockinger et al, 2001;Maher et al, 2009), we report here that short hairpin RNA (shRNA)-mediated depletion of E-cadherin resulted in relocalization of b-catenin from the membrane to the nucleus and activation of b-catenin-TCF signaling, which in turn regulates cell growth in ovarian cancer cells. Theoretically, translocation of b-catenin to the nucleus leads to its association with TCFs and results in regulated transactivation of genes containing the LEF-1/TCF-4 binding sequence near their promoter, such as cyclin D1 (Morin, 1999;Shtutman et al, 1999;Lin et al, 2000).…”
Section: Regulation Of Pten Levels By Cell Density and E-cadherin-cadmentioning
confidence: 78%
See 4 more Smart Citations
“…Recent studies have suggested that E-cadherin suppresses cell growth by inhibiting b-catenin signaling (Gottardi et al, 2001;Stockinger et al, 2001;Maher et al, 2009), we report here that short hairpin RNA (shRNA)-mediated depletion of E-cadherin resulted in relocalization of b-catenin from the membrane to the nucleus and activation of b-catenin-TCF signaling, which in turn regulates cell growth in ovarian cancer cells. Theoretically, translocation of b-catenin to the nucleus leads to its association with TCFs and results in regulated transactivation of genes containing the LEF-1/TCF-4 binding sequence near their promoter, such as cyclin D1 (Morin, 1999;Shtutman et al, 1999;Lin et al, 2000).…”
Section: Regulation Of Pten Levels By Cell Density and E-cadherin-cadmentioning
confidence: 78%
“…These data strongly indicate that loss of E-cadherin promotes the growth of SKOV-3 cells by activating the PI3K/Akt signaling pathway. Because E-cadherin has been shown to inhibit bcatenin signaling (Gottardi et al, 2001;Stockinger et al, 2001;Conacci-Sorrell et al, 2003), we therefore examined the effects of E-cadherin loss on b-catenin signaling. Downregulation of E-cadherin in SKOV-3 cells resulted in the loss of b-catenin from sites of cell-cell contact, as assessed by immunocytochemistry ( Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations